2019
DOI: 10.1111/ijac.13196
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CEL2 glass‐ceramic porous scaffolds coated with chitosan microspheres that have a drug delivery function

Abstract: The present work focused on the preparation of CEL2 bioactive glass (SiO2–P2O5–CaO–MgO–K2O–Na2O) scaffolds loaded with chitosan microspheres. Chitosan microspheres, with a mean particle size of 0.55 μm ± 0.25 μm and loaded with acetaminophen, were obtained through the water‐in‐oil single emulsion solvent evaporation method and were adhered to the surface of the scaffolds by a simple dip‐coating technique. The characterization of the microsphere‐loaded scaffolds, before and after immersion in simulated body flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…According to the literature data, the main crystal phase formed during the devitrification of pure Bioglass 45S5 glasses has not been established precisely. Some authors indicated the formation of the Na 2 Ca 2 Si 3 O 9 phase [58][59][60]; others pointed at the Na 6 Ca 3 Si 6 O 18 phase formation [44,46]; and there are works in which Na 4 Ca 4 Si 6 O 18 was determined as the crystalline phase after glass devitrification [23,61]. The current uncertainty can be explained by the close lattice parameters of all three compounds, Na 2 Ca 2 Si 3 O 9 (hexagonal, P31 (152), a = 10.464, c = 13.176) [62], Na 4 Ca 4 Si 6 O 18 (hexagonal, P32 (152), a = 10.464, c = 13.168) [63], and Na 6 Ca 3 Si 6 O 18 (rhombohedral, R-3m (166), a = 10.500, c = 13.184) [64], as well as by the isostructurality of the Na 6 Ca 3 Si 6 O 18 and Na 4 Ca 4 Si 6 O 18 phases and the high-temperature form Na 2 Ca 2 Si 3 O 9 .…”
Section: The Na2sio3-casio3 Systemmentioning
confidence: 99%
“…According to the literature data, the main crystal phase formed during the devitrification of pure Bioglass 45S5 glasses has not been established precisely. Some authors indicated the formation of the Na 2 Ca 2 Si 3 O 9 phase [58][59][60]; others pointed at the Na 6 Ca 3 Si 6 O 18 phase formation [44,46]; and there are works in which Na 4 Ca 4 Si 6 O 18 was determined as the crystalline phase after glass devitrification [23,61]. The current uncertainty can be explained by the close lattice parameters of all three compounds, Na 2 Ca 2 Si 3 O 9 (hexagonal, P31 (152), a = 10.464, c = 13.176) [62], Na 4 Ca 4 Si 6 O 18 (hexagonal, P32 (152), a = 10.464, c = 13.168) [63], and Na 6 Ca 3 Si 6 O 18 (rhombohedral, R-3m (166), a = 10.500, c = 13.184) [64], as well as by the isostructurality of the Na 6 Ca 3 Si 6 O 18 and Na 4 Ca 4 Si 6 O 18 phases and the high-temperature form Na 2 Ca 2 Si 3 O 9 .…”
Section: The Na2sio3-casio3 Systemmentioning
confidence: 99%
“…Considering the investigations by many researchers, bioactive glasses possess potential of many wide applications such as the formation of HCA and bone, but their use as materials for coating, is more attractive than other applications, especially when they are used as an implant. Their mechanical integrity becomes important [102][103][104][105] when they are used as coating on tougher substrate [106][107][108]. The studies about coatings have proved that depending on the approach of coatings and deposition, the main chemical and physical characteristics will change [109][110][111][112][113].…”
Section: Bioactive Glass Coatingmentioning
confidence: 99%